Banking Profitability Analysis: Company Cases on the Stock Exchange Indonesian Securities (BEI) - Runtunuwu, Prince Charles Heston; Hussin, Hanafi (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2024)
This study aims to investigate the impact of Loans to Deposit Ratio (LDR) on Return On Assets (ROA) in the context of banking institutions. LDR is used as an indicator of a bank's ability to meet obligations and credit demands, while ROA reflects the level of bank profitability. The signal theory is also adopted to explain the asymmetry of information between company management and other stakeholders. The data used in this study was obtained from banking institutions with sample consists of 25 banking companies listed on BEI during the 2016-2019 period. The results indicate that LDR has a significant impact on ROA. Higher LDR values indicate a larger amount of third-party funds channeled into credit, which in turn increases profitability through higher interest income. These findings are consistent with previous research indicating a positive relationship between LDR and ROA. The results of this study contribute to the understanding of factors influencing the financial performance of banking institutions. Banking practitioners and investors can use these findings as a basis for making better decisions in managing risks and enhancing profitability.